Modular Component-Based Quantum Circuit Synthesis - Kang, Chan Gu; Oh, Hakjoo (Proceedings of ACM on programming languages, 2023)
In this article, we present a novel method for synthesizing quantum circuits from user-supplied components. Given input-output state vectors and component quantum gates, our synthesizer aims to construct a quantum circuit that implements the provided functionality in terms of the supplied component gates. To achieve this, we basically use an enumerative search with pruning. To accelerate the procedure, however, we perform the search and pruning at the module level; instead of simply enumerating candidate circuits by appending component gates in sequence, we stack modules, which are groups of gate operations. With this modular approach, we can effectively reduce the search space by directing the search in a way that bridges the gap between the current circuit and the input-output specification. Evaluation on 17 benchmark problems shows that our technique is highly effective at synthesizing quantum circuits. Our method successfully synthesized 16 out of 17 benchmark circuits in 96.6 seconds on average. On the other hand, the conventional, gate-level synthesis algorithm succeeded in 10 problems with an average time of 639.1 seconds. Our algorithm increased the speed of the baseline by 20.3x for the 10 problems commonly solved by both approaches.